The effect of yeast generations on fermentation, maturation and volatile compounds of beer - Krzysztof Kucharczyk; Tadeusz Tuszyński; Krzysztof Żyła; Czesław Puchalski (Czech Journal of Food Sciences, 2020)
The aim of the study was to determine the effect of yeast generations on fermentation and maturation processes, the content of volatile compounds of beer and viability and vitality of yeast biomass on an industrial scale. The experiments with fermentation and maturation were performed in fermentation tanks. The wort was aerated with sterile air. Yeast (S. pastorianus) bottom fermentation was used in fermentation. For pitching four generations (passages) of yeast were used as follows: 1st, 2nd, 3rd and 4th generation. The processes of fermentation and maturation were carried out in the same technological conditions (temperature and pressure). During fermentation and maturation, the changes in the content of the extract, yeast growth and vitality and selected volatile compounds like esters, alcohols and carbonyl compounds were investigated. With the increase in the number of yeast generations, especially from the 2nd generation used in the fermentation process, the content of acetaldehyde and esters increased. Despite the slight differences between generations, the changes are statistically significant. The content of diacetyl is stable for the 1st, 2nd and 3rd generation and higher for the 4th generation. Diversified yeast generations used in the process of fermentation did not affect significantly the final quality of beer.